Adhesionless and near-ideal contact behavior of graphene on Cu thin film. (October 2017) - Hammad, M.; Adjizian, J.-J.; Sacré, C.-H.; Huet, B.; Charlier, J.-C.; Raskin, J.-P.; Pardoen, T.
Abstract: Graphene coatings reduce surface adhesion owing to a low surface energy. In the present work, a single CVD-grown graphene layer on Cu is shown to modify the elastic contact behavior by eliminating adhesion. Nanoindentation load-displacement curves exhibit higher load bearing capacity for Cu/graphene in the elastic regime compared to bare Cu and a closer agreement with Hertz law. Molecular dynamics simulations confirm the quasi-absence of adhesion between graphene and indentor tip. These results open new opportunities regarding tribological issues related to coatings or MEMS applications. Graphical abstract: